The Use of Smartphone Applications in Laboratory Activities in Developing Scientific Communication Skills of Students - Adam Malik*; Mujib Ubaidillah (Universitas Syiah Kuala, 2021)
Smartphone applications have been widely used in everyday life, not least in the world of education. The use of smartphone applications in improving the quality of learning has become a trend and is widely used by educators. The use of smartphones in learning is dominated by the implementation of regular learning and is still lacking in the laboratory's implementation. This study aimed to determine the use of smartphone applications in laboratory activities in developing students' scientific communication skills. The research method used was the quantitative descriptive method. The research sample was a fifth-semester physics education study program student who contracted the school physics laboratory course. The smartphone application used in laboratory activities in this study consists of a physics toolbox and tracker. Physics toolbox is an application whose working principle is based on sensors. Students use the tracker to make graphs from videos that illustrate activities laboratory. The research instrument used was a performance assessment in the form of a scientific communication skill observation sheet. The data analysis technique was done by calculating the percentage of achievement of students' scientific communication skills. The results showed that smartphone applications could develop students' scientific communication skills in a good category. Thus, smartphone applications in laboratory activities can develop one of the skills needed by students in facing the era of industrial revolution 4.0.